Comparative Study of Optimization of data query for SPARQL for Distributed Queries - Pandey, Rakesh Kumar; Azad, Sachindra Kumar (International Journal of Computer Sciences and Engineering, 2025)
Semantic search tool is a user-friendly tool which helps to improve search accuracy by understanding what the user wants to search in the search space on the web or a closed system. But there are large number of challenges for translating the data query to SPARQL for better readability and visual ability. SPARQL is a RDF query language i.e. a semantic query language for database, which is able to retrieve and manipulate data stored in Resource Description Framework(RDF) format. Present work provides the optimum result of running queries over different SPARQL end points. This paper presents the comparative study of different algorithms for optimization and also discusses the two aspects of the result optimization like ranking and readability and it concludes the result for the user data.